Orthotanasia and dignified death in cancer patients: The perception of health professionals. - Alves de Almeida, Hélen Rimet; Freitas de Melo, Cynthia (Psicooncologia, 2019)
Objective: to analyze the perception about dignified death and orthothanasia in the view of health professionals who provide curative and palliative care in oncology. Method: this is a research with exploratory, qualitative approach. Saturation criteria included the participation of eight health professionals from the Cancer Institute of Ceará, Brazil: a physician, a nurse, a social worker and a psychologist of the palliative care team, and an oncologist, a nurse, a social worker and a psychologist of the curative care team. Three instruments were used: semi-structured interview; Free Word Association Test (WAT) with "cancer" and "orthothanasia" as inductive stimulus; and a Photo Projection Test (PPT) using five images. A textual analysis was carried out using the Iramuteq software to analyze the interviews. For the analysis of the WAT, the frequencies of the words of each stimulus were counted; then they were submitted to the word reduction technique and understood through simple frequency analysis. For the analysis of the PPT, the frequencies were counted, followed by analysis of meanings. Results: cancer is perceived by professionals as synonymous with death, pain and suffering, and orthothanasia as a practice of care and affection. The importance of the transition from curative care to exclusive palliative care is evident when there is no prognosis of cure, so as to offer quality of death and pain relief. This process can be facilitated by the acceptance of death and participation on the part of the family. The family must also receive care. Conclusion: health professionals recognize the importance and challenges of orthothanasia.